2012
DOI: 10.1111/j.1365-3040.2012.02535.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal nature of reactive oxygen species production and programmed cell death in elm (Ulmus pumila L.) seeds during controlled deterioration

Abstract: Seed deterioration is poorly understood and remains an active area for research. Seeds of elm (Ulmus pumila L.) were aged at 37°C above water [controlled deterioration treatment (CDT)] for various lengths of time to assess programmed cell death (PCD) and reactive oxygen species (ROS) product in embryonic tissues during a 5 d period. The hallmarks of PCD were identified in the elm seeds during CDT including TUNEL experiments, DNA laddering, cytochrome c (cyt c) leakage and enzymatic activities. These analyses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 65 publications
(148 reference statements)
5
83
1
2
Order By: Relevance
“…In order to develop new tools for monitoring seed aging, qRT-PCR can be used to inspect the expression level of related antioxidative genes (Dona et al, 2013). Recently, Hu et al (2012) reported that controlled deterioration treatment immediately invokes significant increases in caspase-3/DEVDase proteolytic activity. Therefore, qRT-PCR can also be used to detect the expression of the protein in stored seeds.…”
Section: Genomic Methylation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In order to develop new tools for monitoring seed aging, qRT-PCR can be used to inspect the expression level of related antioxidative genes (Dona et al, 2013). Recently, Hu et al (2012) reported that controlled deterioration treatment immediately invokes significant increases in caspase-3/DEVDase proteolytic activity. Therefore, qRT-PCR can also be used to detect the expression of the protein in stored seeds.…”
Section: Genomic Methylation Analysismentioning
confidence: 99%
“…DNA alternation has been reported to trigger PCD during seed deterioration Hu et al, 2012). The two basic strategies used to detect DNA alternation efficiently are the identification of DNA laddering, using electrophoreses, and the identification of DNA alteration, using RAPD markers.…”
Section: Molecular Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed deterioration process is poorly understood; however, it is an important area of research (Hu et al, 2012). Moreover, J. curcas is progressively gaining importance in several countries due to its high oil content and suitability for biodiesel production (Kumar & Sharma, 2008;Parawira, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are various mechanisms involved in the loss of seed viability during storage; among these mechanisms are lipid peroxidation, enzyme inactivation or protein degradation, cell membrane rupture, and the loss of DNA integrity (McDonald, 1999;Mittler, 2002;Bailly, 2004;Hu et al, 2012;Kumar, Prasad, Banerjee, & Thammineni, 2015). The generation of reactive oxygen species (ROS) and resulting lipid peroxidation, together with the ability of the seeds to remove these radicals, are considered the main causes of seed deterioration (McDonlad, 1999;Bailly, 2004), especially for oilseeds such as J. curcas seeds.…”
Section: Introductionmentioning
confidence: 99%